Heat stress management in poultry farms: A comprehensive overview. (August 2019) - Saeed, Muhammad; Abbas, Ghulam; Alagawany, Mahmoud; Kamboh, Asghar Ali; Abd El-Hack, Mohamed E.; Khafaga, Asmaa F.; Chao, Sun
Abstract: Heat stress causes significant economic losses in poultry production, especially in tropical and arid regions of the world. Several studies have investigated the effects of heat stress on the welfare and productivity of poultry. The harmful impacts of heat stress on different poultry types include decreased growth rates, appetites, feed utilization and laying and impaired meat and egg qualities. Recent studies have focused on the deleterious influences of heat stress on bird behaviour, welfare and reproduction. The primary strategies for mitigating heat stress in poultry farms have included feed supplements and management, but the results have not been consistent. This review article discusses the physiological effects of heat stress on poultry health and production and various management and nutritional approaches to cope with it. Highlights: Heat stress is a major issue of poltry farming in tropical and arid regions of the world. It causes significant economic losses in terms of low production and high mortality. Today, research has focused on coping strategies to overcome the deleterious effects of heat stress in commercial farming. The mitigating strategies against heat stress includes use of dietary supplements, management techniques etc. This review has focused on coping methods against heat stress to reduce its' deleterious effects on poultry production.